EDUCATION HOW TO SEPARATE HOUSEHOLD WASTE FOR THE COMMUNITY DEVELOPMENT BASED ON COMMUNITY DEVELOPMENT. - Erwani Merry Sartika; Audyati Gany; Novie Theresia Br Pasaribu (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2022)
Garbage can be said as a leftover or wasted goods can couse big problems in the future if it not being managed properly, Naturally, household waste and other types of waste have different decomposition times, and there is even waste that can be categorized as non-biodegradable by nature. Waste that is managed wisely by using the principles of Reduce, Reuse, Replace and Recycling things that are considered wasted and not useful can still be something meaningful. The rapid rate of garbage accumulation can cause some disease, damaging the environment and nature, and cause unpleasant sights and odors. Education is an action that given to the community so they have the knowledge and care to protect the environment. In educating the community, it is also necessary to be motivated so that the community has enthusiasm and passion. The education that has been given to the community of Sukajadi Subdistrict, Bandung, has caused the participants' knowledge to increase by 24%. The continuation of the education that has been given is education on how to coordinate sorted waste so that it can be a blessing and can be something that can be used in different functions.